Improving Surgical Outcome Using Diffusion Tensor Imaging Techniques in Deep Brain Stimulation - See, Angela An Qi; King, Nicolas Kon Kam (Frontiers in Surgery, 2017)
Introduction: Recent advances in surgical imaging include the use of diffusion tensor imaging (DTI) in deep brain stimulation (DBS) and provide a detailed view of the white matter tracts and their connections which are not seen with conventional magnetic resonance imaging. Given that the efficacy of DBS depends on the precise and accurate targeting of these circuits, better surgical planning using information obtained from DTI may lead to improved surgical outcome. We aim to review the available literature to evaluate the efficacy of such a strategy. Methods: A search of PubMed was performed to identify all articles using the search terms “(diffusion tractography OR diffusion tensor imaging OR DTI) AND (deep brain stimulation OR DBS)”. Studies were included if DTI was used and clinical outcomes were reported. Results: We identified 35 studies where the use of DTI in DBS was evaluated. The most studied pathology was movement disorders (17 studies), psychiatric disorders (11 studies), and pain (7 studies). The overall responder rates for tremor reduction was 70.0% (sd = 26.1%) in 69 patients, 36.5% (sd = 19.1%) for obsessive compulsive disorder in 9 patients, 48.3% (sd = 40.0%) for depression in 40 patients, and 49.7% (sd = 35.1%) for chronic pain in 23 patients. Discussion: The studies reviewed show that the use of DTI for surgical planning is feasible, provide additional information over conventional targeting methods, and can improve surgical outcome. Patients in whom the DBS electrodes were within the DTI targets experienced better outcomes than those in whom the electrodes were not. Many current studies are limited by their small sample size or retrospective nature. The use of DTI in DBS planning appears under-utilized and further studies are warranted given that surgical outcome can be optimized using this non-invasive technique.